STUDI TENTANG PERUBAHAN KADAR IODIUM DAN SIFAT ORGANOLEPTIK PADA PROSES PEMBUATAN DAN WAKTU SIMPAN TELUR ASIN - Wikanastri H; Nurrahman - (JURNAL LITBANG, 2006)
Making of salt egg by iod propouse for preservation or long of storage and properties of organoleptic egg. So effirt, preventive to ill that malnutrition of iod (GAKI) The research propouse to lvtow effectfrom addition of iod in salt on KIO3 concentration and properties of organoleptic on salt egg. The research was done in two leve, the /irst level was making of salt egg by addition KIO3 5.000, 10.000, 15.000 and 20.000 ppm. The tvvice level, the salt eggs was done storage a long of 5, 10, l5 and 20 days.The result of research could to lvtow that effect of interaction between KIO3 concentration and long of storage had been KIO3 concentration in salt egg. Dffirence of KIO3 concentration did not be elfect of organoleptic properties. Long of storage did be effect of organoleptic properties.Keywords: iod, storage and egg